Berardinelli Seip Syndrome: A rare case report - Samreen Ashraf; Shadab Masood; Farrah Naz; Junaid Rashid (Journal of the Pakistan Medical Association, 2022)
Berardinelli Seip Congenital Lipodystrophy (BSCL) or Congenital Generalized Lipodystrophy (CGL) is one of the four subgroups of lipodystrophy syndrome which is characterized by varying degrees of loss of adipose mass in the body. It is an extremely rare autosomal recessive disorder and commonly reported clinical presentations include muscular hypertrophy, gigantism, hepatomegaly, impaired glucose tolerance, acanthosis nigricans, hypertriglyceridaemia, cardiomyopathy, intellectual impairment, bone cysts and phlebomegaly. We present a case of a 4.5 years old male child born to consanguineous parents. He presented with the right lung consolidation and pancytopenia with a normal bone marrow biopsy, which was resolved with intravenous antibiotics. He had acromegaly-like features, hirsutism, history of recurrent diarrhoea and chest infections with isolated IgA deficiency, firm hepatomegaly, a well-defined bone cyst in the proximal right femur and hypertriglyceridaemia. This is the first case of BSCL, reported in Pakistan with a bone cyst and IgA deficiency. —Continue